1990
DOI: 10.1002/elan.1140020707
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of electrochemical oxidation of trimethoprim at pyrolytic graphite electrode

Abstract: The electrochemical oxidation behavior of trimethoprim has been investigated at a pyrolytic graphite electrode over a wide pH range (1.35-10.71). Below pH 3.2, trimethoprim is electrooxidized in two well-defined steps, each involving 4e, 4 H f . Only one well-defined oxidation peak was observed above pH 3.5 however. Products corresponding to each peak have been separated and characterized by thinlayer chromatography (TLC), infra red (IR), and mass spectra. A tentative mechanism associated with the voltammetric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…TMP was electro‐oxidized in the pH range 3–10 to mononitroso derivative by 4e mechanism. The mononitroso derivative underwent electro‐oxidation to dinitroso derivative by 4e mechanism at pH less than 3 32. Based on our experimental observation of the involvement of 4e and on the previous report of identification of products of electro‐oxidation of TMP, we propose a possible mechanism for it (Figure 5).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…TMP was electro‐oxidized in the pH range 3–10 to mononitroso derivative by 4e mechanism. The mononitroso derivative underwent electro‐oxidation to dinitroso derivative by 4e mechanism at pH less than 3 32. Based on our experimental observation of the involvement of 4e and on the previous report of identification of products of electro‐oxidation of TMP, we propose a possible mechanism for it (Figure 5).…”
Section: Resultssupporting
confidence: 65%
“…The amino group at position 4 of the pyrimidine ring may be more easily oxidized than the one at position 2 which is a part of stable pyrimidine system. Again, a 4e oxidation of the mononitroso derivative can lead to the formation of dinitroso derivative 32. But then, there should be two distinct peaks in the voltammogram corresponding to the formation of mono and dinitroso derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary experimental studies were performed in order to understand the electrochemical behaviour of trimethoprim drug using an unmodified CPS. A simple CV measurement showed a peak at around +1.2 V, indicating oxidation of the drug ( Figure 2 ) with irreversible nature, in accordance with other studies [ 25 , 35 , 39 ].…”
Section: Resultssupporting
confidence: 91%
“…The voltammetric behavior of trimethoprim investigated at the [5,10,15,20-tetrakis(4-methoxyphenyl)porphyrinato]Mn(III)chloride-modified glassy carbon electrode (TMOPPMn(III)Cl/GCE) showed that TMOPPMn(III)Cl acts as an electrocatalyst for the oxidation of trimethoprim . There are two amino groups, one at position 4 of the pyrimidine ring and the other at position 2 of the stable pyrimidine system . Deprotonation of the NH 2 group attached to either C4 or C2 of trimethoprim can occur, and thus both of these possibilities were investigated computationally.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, for further calculations, we have considered the removal of a proton from the C4 amino group. The detailed mechanism is outlined in Scheme . The first step involved in the conversion of trimethoprim (I) to nitroso derivative (IX) is the deprotonation of the NH 2 group at the fourth position to give the trimethoprim anion (II).…”
Section: Resultsmentioning
confidence: 99%